Predictors of Purchase Decision: The Combined Effects of Business Sustainability Support and Purchase Intention - Miranti, Liana; Cahya, Bayu Tri; Soetjipto, Budi Eko; Diah Saputri, Dilla Ajeng (Klabat Journal of Management, 2024)
This study investigates the effects of business sustainability support (Customer Relationship Management (CRM), Brand Equity, and Corporate Social Responsibility (CSR)) on purchasing decisions, with Purchase Intention serving as a mediating variable, among Tupperware consumers. In the face of intense competition within the plastic-based household goods industry, Tupperware has encountered declining sales, prompting the necessity for innovation and effective marketing strategies. Employing a causal quantitative approach, this study engaged 80 Tupperware consumer respondents and utilized the Structural Equation Model (SEM) for data analysis, employing the Smart PLS 3.0 program. The findings revealed that Brand Equity and CSR exert a positive and significant influence on purchasing decisions, while CRM did not exhibit significance. Furthermore, Purchase Intention was found to mediate the positive impact of CRM, Brand Equity, and CSR on purchasing decisions.